The hunger games: famine 1932–1933 in the historical policy of Ukraine and Russia - Menkouski, Viachaslau I.; Šmigel’, Michal; Dubinka-Hushcha, Lizaveta (Journal of the Belarusian State University. History, 2021)
The modern historical policy of Ukraine and the Russia is analysed. The study uses the methodology of historical memory studies, specifically, research of historical consciousness, collective and historical memory. The methodology is based on the analysis of a situation when ideas about the past as national history depend on the mentality and goal setting of a particular social, national or other group. The object of the study is the modern socio-political situation in Ukraine and Russia associated with the understanding and assessment of the famine of 1932–1933 both in the Soviet Union as a whole, and in Ukraine in particular. The authors consider the modern memorial culture of the two nations, highlight issues of regional and national identity and the formation of myths of national memory as central issues in the paper. The transformation of memorial practices and the legal framework of the Russia and Ukraine after the collapse of the Soviet Union is considered. The authors arrive at the conclusion that the discussion between the Russian and Ukrainian sides to this day has turned into constructing a scheme of the «reverse history» based on the projection of the present state of affairs into the past. It is not possible to find any fundamentally new evidence as long as the Russian archives remained classified, and the parties increasingly resort to a nationalist type of argumentation. Punning on the name of the famous Hollywood blockbuster, we can say that the «hunger games» have become a reality in the modern politics of memory of post-Soviet states.
Keywords: Ukraine; Russia; famine of 1932–1933; Holodomor; genocide; historical policy; memorial culture; historiography